Acceleration and Speed Performance of Brazilian Elite Soccer Players of Different Age-Categories - Loturco, Irineu (J Hum Kinet, 2018)
This study aimed to compare vertical jump ability (squat-jump [SJ] and countermovement-jump [CMJ]), relative to body mass mean propulsive power in the jump-squat (MPP-REL JS), and the 0-5, 5-10, and 10-20 m acceleration and speed among soccer players from the same professional club, divided into age-categories (U15 [n = 20], U17 [n = 53], U20 [n = 22] and senior [n = 25] players). The tests were performed at the start of the preseason in indoor facilities. The magnitude-based inference approach and the standardized differences (based on effect sizes) were used to compare the age-groups. The SJ, CMJ, and MPP-REL JS increased across the age-groups up to U20, the latter being similar to senior players. Interestingly, the 0-5 m acceleration was likely and possibly higher in U15 players compared to U17 and senior players. Although soccer athletes improve their unloaded and loaded jump abilities across the age-categories (plateauing during adulthood), the same does not hold true for acceleration capacity, from the early phases of players’ development (i.e., U15). Strength and conditioning professionals should seek effective strategies to minimize impairment in maximal acceleration performance of elite soccer players throughout their prospective training programs.